Humour and dreams in George Bernard Shaw's Man and Superman and Saint Joan : a Freudian psychoanalysis - Umi Kelsom binti Nayan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2009)
Elements of humour and dreams are George Bernard Shaw's special ways to convey his ideas relating to the morality and beliefs of the modern society in the early twentieth century. As one of prominent literary British figures in the twentieth century, his works demonstrate common issues in life pertaining to sex, marriage, religion, war, poverty as well as history in the form of satirical wit. These humour and dreams are triggered by the conflicts experienced by the characters. Therefore, Shaw's Man and Superman (1903) and Saint Joan (1924) evince the disputes between desire, intellect and authority. Man and Superman displays the ongoing debate between desire and intellect whereas Saint Joan portrays the tension between individual reasoning and the authoritarian Catholic Church. These human conflicts can be elucidated by employing Sigmund Freud's psychoanalysis with the three parts of the mind; the id, the ego and the super-ego. The fact that the id represents the unconscious desires, the ego reflects the intellectual reasoning while the super-ego acts as the conscience, humour and dreams are the results of the schisms between these elements. Hence, in Shaw's plays, the clash between the id and the ego is perceptible in Man and Superman while the discord between the ego and the super-ego is conspicuous in Saint Joan. In Man and Superman, the id and the ego are reconciled to fulfill the Life Force. In Saint Joan, the profound truth of Joan's reasonable convictions is clearly depicted. In short, the conflicts between the three elements initiate satirical humour and dreams that also function as a release and a device for problem-solving. By applying Freudian psychoanalysis to Shaw's plays, the perennial human conflicts between one's desires, mind and beliefs as experienced by the characters and human beings in general will be explicated and expounded.